Tanggap Varietas Kacang Hijau Pada Perlakuan Ekstrak Rhizoma - Utama, M Zulman Harja (Jurnal Embrio, 2008)
Experiment was aimed investigate the response of variety mung bean to extract rhizome coarse grass for growth and production. Experiment was conducted in farmer land of farmer Alai Parak Kopi Padang, from March to June 2006. Experiment was conducted using random completed design of one factor. Result of experiment showed that variety bhakti tolerant of extract rhizome coarse grass